PENGARUH PEMBERIAN GINGERCOOKIES PADA NAUSEA DAN VOMITING WANITA HAMIL TRIMESTER PERTAMA - Supatmi, Supatmi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Ginger as one of the types of herbs that contains essential oils that refreshes and vomiting reflex block while gingerol can improve blood circulation and nerves working properly. Therefore, the purpose of this study was to determine the provision gingercookies against nausea vomiting the first trimester pregnant women. The meth- od was used by researcher was One Group Pre Test - Post Test Design with sampling techniques consecutive sampling. The samples were used by researcher was in the first trimester pregnant women who experienced nausea and vomiting in BPS Rungkut region, Surabaya, the number of respondents as many as 30 respondents. Collecting data used questionnaires beginning and end of the interview sheet. The independent variables was giving of gingercookie and the dependent variable was nausea vomit- ing in pregnant women in the first trimester . Data were analyzed by using the Wilcoxon signed rank test test with a significance value Î± â‰¤ 0.05. The analysis showed that there was the influence of gingercookies between nausea vomiting and in the first trimester pregnant women. The results were expected that the first trimester pregnant women could apply appropriate alternative therapy for reducing nausea vomiting, one with consuming processed ginger gingerbread or another in order to reduce nausea and vomiting.